2017
DOI: 10.1002/brb3.659
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of production of collagen‐rich deposits in peripheral nerves in response to injury: A pilot study in a rabbit model

Abstract: IntroductionAlthough collagen‐rich deposits are the main component of neural scars, the patterns of their formation are ill defined. Essential to the biosynthesis of collagen fibrils are enzymes catalyzing posttranslational modifications and chaperones that control the formation of the collagen triple helix. Prolyl‐4‐hydroxylase (P4H) and heat shock protein‐47 (HSP47) play a key role, and their production is upregulated during scar formation in human tissues. Alpha smooth muscle actin (αSMA) is also produced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…Although αSMA-positive myofibroblasts were not present in the stumps, we cannot exclude the possibility that they were present only transiently outside of our 2-to 10-week postinjury experimental time window. This possibility is in agreement with our study on the crush injury and partial-transection injury modes, where we observed some αSMA-positive fibroblasts 1-2 weeks after injury and with Chamberlain et al (2000), who observed αSMA-positive myofibroblasts only 60 days after injury (Rivlin et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Although αSMA-positive myofibroblasts were not present in the stumps, we cannot exclude the possibility that they were present only transiently outside of our 2-to 10-week postinjury experimental time window. This possibility is in agreement with our study on the crush injury and partial-transection injury modes, where we observed some αSMA-positive fibroblasts 1-2 weeks after injury and with Chamberlain et al (2000), who observed αSMA-positive myofibroblasts only 60 days after injury (Rivlin et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the αSMA-positive staining was visible in the perineurial fibroblasts (data not shown) in which this marker is a natural intracellular component (Rivlin et al, 2017).…”
Section: Patterns Of Distribution Of Cells Expressing αSma and Hsp4mentioning
confidence: 84%
See 3 more Smart Citations